2014
DOI: 10.1530/rep-13-0508
|View full text |Cite
|
Sign up to set email alerts
|

microRNA 376a regulates follicle assembly by targeting Pcna in fetal and neonatal mouse ovaries

Abstract: In mammals, the primordial follicle pool, providing all oocytes available to a female throughout her reproductive life, is established perinatally. Dysregulation of primordial follicle assembly results in female reproductive diseases, such as premature ovarian insufficiency and infertility. Female mice lacking Dicer1 (Dicer), a gene required for biogenesis of microRNAs, show abnormal morphology of follicles and infertility. However, the contribution of individual microRNAs to primordial follicle assembly remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 80 publications
2
25
1
Order By: Relevance
“…In any case, PCNA-mediated oocyte apoptosis depends on the availability of the inhibitor of growth 1 (ING1), a member of an evolutionarily conserved family of tumor suppressor proteins, and results in increasing Bax, casp-3 and Par6 and decreasing Bcl-2 gene expression (Xu et al, 2011). Interestingly, the oocytes were protected from the PCNA dependent apoptosis by the micro RNA 376a that, by directly binding to the 3' untraslated region (UTR) of the PCNA mRNA, inhibits its translation (Zhang et al, 2014).…”
Section: Pcd In Mammalian Fetal Ovary 53mentioning
confidence: 99%
“…In any case, PCNA-mediated oocyte apoptosis depends on the availability of the inhibitor of growth 1 (ING1), a member of an evolutionarily conserved family of tumor suppressor proteins, and results in increasing Bax, casp-3 and Par6 and decreasing Bcl-2 gene expression (Xu et al, 2011). Interestingly, the oocytes were protected from the PCNA dependent apoptosis by the micro RNA 376a that, by directly binding to the 3' untraslated region (UTR) of the PCNA mRNA, inhibits its translation (Zhang et al, 2014).…”
Section: Pcd In Mammalian Fetal Ovary 53mentioning
confidence: 99%
“…The female fertility of mammalian species is a dynamic and well-coordinated process miR-376a in neonatal mouse primordial follicles was reported by Zhang et al (2014).…”
mentioning
confidence: 99%
“…In another study conducted by the same group, miR-376a was found to downregulate PCNA expression and its expression was reciprocally correlated with that of PCNA mRNA in fetal mouse ovaries. Furthermore, cultured 18.5 dpc ovaries transfected with miR-376a exhibited reduced apoptosis of oocytes and an increase in the number of primordial follicles; this effect was mediated by miR-376a-inhibition of PCNA (Zhang et al 2014a). These findings imply that by inhibiting oocytes' apoptosis miR-376a acts as a positive regulator of primordial follicles assembly.…”
Section: Assembly Of Primordial Folliclesmentioning
confidence: 94%